Dalalah 'Ibarah Al-Nass: Sebuah Metode Penemuan Hukum Islam - Nafisah, Durotun (Al-Manahij: Jurnal Kajian Hukum Islam, 2007)
Al-Qur'an and hadis as main sources of Islamic laws seem global in terms of determination. Dalalah 'Ibarah al-nass is a method in determining dear and direct meaning. Asbab al-nuzul is a way to understand those meanings.